Revisão das espécies de Camelobaetidius Demoulin (Ephemeroptera: Baetidae) com o filamento mediano reduzido - Boldrini, Rafael (Instituto Nacional de Pesquisas da Amazônia - INPA, 2020)
The genus Camelobaetidius Demoulin, 1966 has 38 valid species distributed throughout the Neotropical Region, being one of the most studied genera of the Baetidae family. The incomplete descriptions of some Camelobaetidius species, and the great morphological variation among them, make specimens identification to the specific level difficult. Currently there are eight species of the genus which the nymphs have the reduced median filament, restricted to South America. The aim of the study was to review the eight species of Camelobaetidius with reduced median filament, and propose the descriptions of nymphs and adults in a standardized and detailed way. In this study, Camelobaetidius apis is considered a junior synonym of C. billi. Six nymphs are redescribed based on nymphs: C. billi, C. francischettii, C. ipaye, C. leentvaari, C. maranhensis, C. rufiventris. The nymph of C. mantis was not examined, and is presented only one diagnosis and comments for this species. For the first time, the imagos of C. francischettii are described, and the male imago of C. billi is redescribed. A key for the species of Camelobaetidius with reduced median filament is presented.